Rare faction of flora of the designed landscape reserve “Balka Shchurovka” - Kyiak, S. V. (Quality in Sport, 2024)
The article is devoted to the study of the modern distribution of certain rare plant species within the "Balka Shchurovka" beam system (near the settlements of Dniprovske, Novomykolaivka of the Verkhnyodniprovska OTG of the Dnipropetrovsk region) and substantiation of the prospects for granting the object the status of a nature conservation area. The natural diversity of the vegetation cover of the designed reserve consists of zonal steppe vegetation, bairach forests, psamophilic and petrophilic communities, and meadow vegetation. According to indicators of biodiversity, the territory b. Shchurovka is one of the most valuable within the borders of Verkhnyodniprovska OTG of Dnipropetrovsk region. In the process of researching the flora of the planned reserve, a number of new locations of species rare for the region and the region were discovered. 26 regionally rare plant species grow here, 13 species listed in the Red Book of Ukraine, 3 species from Resolution 6 of the Berne Convention and Annexes of the Habitats Directive, presented in the flora of Ukraine, 1 species from the World Red List. The list of plants of the Dnipropetrovsk region included in the Red Book of Ukraine includes 56 species of vascular plants, of which 13 species grow within the b. Rat, which is 23% of the total number of red book species of Dnipropetrovsk region. An important and interesting feature of the layer of sand exposed on the right slope of the gully is the presence of blocks of red sandstone enriched with iron oxides. Near the sandstone outcrops, a characteristic complex of flora has formed on sandy soil with the participation of Sempervivum ruthenicum Schnittsp. & C.B. Lehm, Pulsatilla pratensis (L.) Mill. s.l., Thymus pallasianus Heinr.Braun, Peucedanum arenarium Waldst. & Kit. (Taeniopetalum arenarium (Waldst. & Kit.) V. N. Tichomirov), Achillea leptophylla M. Bieb. Jurinea cyanoides (L.) Rchb and Pulsatilla patens (L.) Mill grow here. s.l. - rare species from the Annexes of the Habitats Directive, Annex I of the Berne Convention, which prefer biotopes with an intact structure as part of rare coenoses. The study of the rare fraction of the flora of the beam system in the context of the conservation of biodiversity of the Right Bank Steppe of the Dnieper region can become the basis of the nature conservation concept of sustainable development of the region.